If a tree falls in a forest: implications of forest structure persistence for the Pacific marten (Martes caurina). Issue 8 (1st August 2019) - Delheimer, Matthew S.; Moriarty, Katie M.; Linnell, Mark A.; Woodruff, Bryce V.
Abstract: A global decline in large trees, largely driven by anthropogenic influences, has potentially dire consequences for cavity‐dependent wildlife. For several species of conservation concern in western North America, including Pacific martens ( Martes caurina ), fishers ( Pekania pennanti ), and spotted owls ( Strix occidentalis ), large live and dead trees (snags) with cavities are forest structural elements that are requisite to fulfilling life history requirements. More than a century may be necessary for trees to develop cavities of a suitable size for use by martens, fishers, and owls, yet the relative amount of time that such trees persist as usable prior to senescence is largely unknown, despite the implications for how forests are managed as habitat for these wildlife species. To address this uncertainty, in 2016, we re‐located 44 live trees and snags identified as marten rest structures between 2009 and 2012 in the Lassen National Forest, California. Upon re‐location, we assessed structure persistence by determining whether structures had changed type (e.g., a live tree that died and transitioned to a snag) or usability (any structure that was degraded to a point where it was no longer usable by a marten). After 5–7 yr, 25% ( n  =   11) of marten rest structures changed type and 16% ( n =  7) appeared to be unusable—a stark contrast compared to a similar study investigating persistence of fisher rest structures, which documented one‐third of the change in structure type and no change in usability over roughly twice the return interval (8–12 yr). Our results emphasize the vast disparity between the lengthy period required for trees to become suitable for marten use and the potentially short period for which they may remain usable. We suggest that forest managers consider the importance of these fine‐scale forest structural elements when developing broad‐scale strategies to reduce fire risk and improve resilience in western North American forests.